Dairy farm roadway surface materials as a P-source within the nutrient transfer continuum framework - Fenton, Owen; Rice, Paul; Murnane, John. G.; Tuohy, Patrick; Daly, Karen (Frontiers in Environmental Science, 2022)
Internal farm roadways are connectors within agricultural landscapes, which act as sub-components of the nutrient transfer continuum (NTC). On dairy farms, roadway surface runoff dissolved and particulate phosphorus (P) sources stem from a combination of cow excreta deposited at locations that impede animal flow, soil deposited from cow hooves or machinery tyres, run-on from up-gradient fields, public roadways or farmyards and incidental spill of organic/inorganic fertilizers. The present study investigates the storage and potential release of P from the underlying roadway material (i.e. composite of soil and stone aggregates) as this source component is not considered in the NTC framework or documented in the literature. Herein, farm roadway materials were sampled (to 1 cm depth) at 17 locations avoiding fresh cow excreta. Multiple location types were selected e.g. straight roadway sections, roadway junctions, before and adjacent standoff areas associated with cattle underpasses, with all locations varying in distance from the farmyard. Roadway samples were analysed for phosphorus (P) and metals (Al, B, Ca, Co, Cu, Fe, K, Mg, and Mn) content. Results showed that the soil component of roadway materials are significant P legacy sources and are in themselves a P-storage component that merits inclusion in the NTC framework. All sampled locations, when compared with fresh roadway stone aggregates or surrounding fields, had highly elevated P with plant available Morgans P > 8 mg L-1 (Index 4, ranging from 10 – 110 mg L-1). Sampling points within 100 m of the farmyard together with roadway junctions and underpasses beyond this distance had highest P concentrations. Critical source areas, where source, mobilisation and transport of P to waters coincided, formed at three locations. Possible mitigation measures are a) divert roadway runoff into fields using low-cost surface water breaks, b) disconnect cattle underpass tanks from receiving waters and c) change roadway infrastructure to improve cow flow and minimise source build-up. Future research should examine P loads in runoff from roadway sections across farm typologies and roadway material types.